Transforming okara into a microalgae culture medium - Kim, Jaejung (2019)
Okara is a soybean residue generated in the soymilk and tofu production. Despite the rich nutritional content of okara, majority of it is underutilized and discarded due to its insolubility. In this study, solid-state fermentation with food-grade fungi was utilized to solubilize the nutrients in okara. The fermented okara was then used as a nutrient-rich culture medium for the microalgae Phaeodactylum tricornutum (P. tricornutum). The results showed significantly higher biomass production in the fermented okara medium (0.52 g L-1) as compared to the conventional medium F/2 (0.25 g L-1), leading to a 2-fold increment. Moreover, fucoxanthin productivity remarkably increased by 4.8-fold from 0.24 mg L-1d-1 to 1.17 mg L-1d-1. The fatty acid composition of the cells showed that saturated fatty acids and monounsaturated fatty acids comprised greater proportion of the cells grown in F/2 medium whereas polyunsaturated fatty acids comprised greater proportion of the cells grown in fermented okara medium. This study demonstrates an innovative and low-cost strategy of using fermented okara as a nutrient-rich substrate for achieving high-density algae cultivation and for increasing the production of high-value compounds in a sustainable way.